The mediating role of emotional intelligence and marital adjustment in the relationship between mindfulness in marriage and subjective well-being - Erus, Seher Merve; Deniz, Mehmet Engin (Pegem Journal of Education and Instruction, 2020)
This study examined the mediating role of emotional intelligence and marital adjustment in the relationship between mindfulness and subjective well-being; interpersonal mindfulness in marriage and subjective well-being. 550 married individuals (370 female and 180 male) participated in this research. “Mindfulness Attention Awareness Scale”, “Mindfulness in Marriage Scale”, “Trait Emotional Intelligence Questionnaire-Short Form”, Marital Adjustment Test”, “Positive and Negative Affect Scale”, “Life Satisfaction Scale” and “Personal Information Form” were used in this research. Pearson product-moment correlation coefficient and path analyses, which is one of the structural equation model technics, were used for data analyses. Correlation analysis results showed that there was positively correlation between mindfulness, interpersonal mindfulness in marriage, emotional intelligence, marital adjustment and subjective well-being. Path analysis result showed that emotional intelligence fully mediated the relationship between mindfulness and subjective well–being. Besides, emotional intelligence and marital adjustment partially mediated the relationship between mindfulness in marriage and subjective well–being and model explained 51.00 % of total variance of subjective well-being. The results of the research were discussed in the light of literature and suggestions were presented.